Hiking experience: don't avoid eating rice! / Hussin Khan Rahmatullah Khan … [et al.] - Rahmatullah Khan, Hussin Khan; Razali, Mohamad Azli; Zainol, Noorliza; Abdul Hadi, Arnieyantie (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2025)
Mountain hiking in Malaysia has become a popular physical activity that attracts people from various groups, genders, and races. In this piece, I want to share the significance of eating rice during hiking, especially when the trek is challenging. Hiking for three days and two nights in the forest requires meticulous planning, particularly in terms of nutrition. Ensuring an adequate supply of food, especially rice, is crucial. Rice is a primary source of carbohydrates essential for sustaining intense physical activity like hiking. During the hike, I learned firsthand how crucial it is to maintain a proper diet, especially when undertaking such demanding physical activities. One evening, after a long day of hiking, me and my group prepared a meal that included a travel pack (Rice), instant noodle, meatball, energy drink, energy bar, Milo 3 + 1, coffee, and tea. This meal was essential in restoring our depleted energy levels. However, I made the mistake of not eating rice the next morning. Instead, I opted for bread, tuna spread, and oat biscuits, thinking they would suffice. This decision proved to be a grave error.